Family identification: a beneficial process for young adults who grow up in homes affected by parental intimate partner violence - Naughton, Catherine M.; O’Donnell, Aisling T.; Muldoon, Orla T. (Frontiers in Psychology, 2015)
Exposure to parental intimate partner violence (parental IPV) is a complex trauma. Research within social psychology establishes that identification with social groups impacts positively on how we appraise, respond to and recover from traumatic events. IPV is also a highly stigmatized social phenomenon and social isolation is a major factor for families affected by IPV, yet strong identification with the family group may act as a beneficial psychological resource to young people who grew up in homes affected by IPV. The current study, an online survey of 355 students (Mage = 20, 70% female), investigated if a psychosocial process, specifically identification with the family, may influence the relationship between the predictor, exposure to parental IPV, and outcomes, global self-esteem and state anxiety. Mediation analysis suggests that identification with the family has a positive influence on the relationship between exposure to parental IPV and psychological outcomes; exposure to parental IPV results in reduced family identification, but when family identification is strong it results in both reduced anxiety and increased self-esteem for young people. The findings highlight the importance of having a strong sense of belonging to the extended family for young people who were exposed to parental IPV, thus has implications for prevention, intervention, and social policy.